Myths of peace & democracy? : towards building pillars of hope, unity and transformation in Africa - Marongwe, Ngonidzashe; Marongwe, Ngonidzashe; Mawere, Munyaradzi; Mawere, Munyaradzi (Langaa Research & Publishing CIG, 2016)
The myths of peace and democracy in Africa are at the heart of this volume. Democracy and peace have become buzz words across postcolonial Africa. The gospel of democracy and peace is preached by national governments and by civil society and international organisations alike. But to what extent are the ongoing sideshows and charades of quasi-oligarchies in Africa really democracy? What do ordinary Africans mean when they hunger and thirst for democracy and peace? Positive and noble as the loud sounding rhetoric about democracy and peace in Africa might seem, the reality of propaganda and dissemblance and of multi-dimensional violence are simply too overwhelming not to be disillusioning. This book interrogates the rampant violence, enduring conflicts, autocratic governance, and facades of democracy amidst claims and calls for enduring peace on the continent. This is a monumental resource book for human rights activists, conflict management practitioners, civil society activists, political scientists, statesmen and development practitioners. It poses a challenge to those African governments who claim to embrace principles of democracy and respect for human rights to rethink and reconsider their role as ambassadors of peace, hope, transformation, and good governance.